Organizational Learning as a Strategic Choice in Public Sector Organization: Changing Cultural Attributes in a State Owned Agricultural Bank of Bangladesh - Ahsan, Md. Ali (American Journal of Trade and Policy, 2018)
Network governance has become an important paradigm in recent reform effort; inter-sectoral collaboration is the key theme of such initiative. As part of the developing world, Government of Bangladesh is taking initiatives to prepare its civil service competent to meet the challenges of a welfare state for a sustainable society. Taking this in an account, this study focuses on the recent reform program in public sector organization initiated by the government. The core objective of this study is to understand the phenomenon of organizational culture that has an influence on organizational learning and innovation from the viewpoint of experienced civil servants who have gone through the change process and become an active implementer of learning and innovation in their organization to meet the desire change situation.
Keywords: Organizational Learning; Strategy; Organizational Reform; Public Sector Organization